Circular Economy Implementation in Indonesian Manufacturing: A Systematic Literature Review of Drivers, Barriers, and uture Research Directions - Supriadi Siagian; Durahman Marpaung; Prianda Pebri; Taufiq Hidayah; Purwanto, Purwanto; Fandra Dikhi Januardani; Sabrina, Sabrina (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The circular economy (CE) has emerged as a crucial paradigm for achieving resource efficiency and sustainability within Indonesia’s manufacturing sector. However, its implementation faces structural, technological, and regulatory challenges that hinder sustainable transformation. This study systematically reviews literature on CE implementation in Indonesian manufacturing to identify its drivers, barriers, and future research directions. Using the Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework, data were collected from Scopus, Web of Science, and Google Scholar covering 2018–2024. Out of 462 records, 32 studies met the inclusion criteria after screening and quality assessment. Findings indicate that government policy support, digital technology readiness, and supply chain collaboration are key drivers, while limited funding, low organizational awareness, and fragmented regulation remain major barriers. This review contributes by proposing an integrative conceptual framework and outlining future research on circular business models and cross-sectoral policies to accelerate in Indonesia’s green economy transition.